Detection of primary malignancy and metastases with FDG PET/CT in patients with cholangiocarcinomas: Lesion-based comparison with contrast enhanced CT - Youssef Elias; Aladin Mariano; Yang Lu (World Journal of Nuclear Medicine)
The current National Comprehensive Cancer Network (NCCN) Guidelines consider the role of 2-deoxy-2- 18 F-fluoro-d-glucose positron emission tomography/computer tomography (FDG PET/CT) in the evaluation of cholangiocarcinoma (CCA) as "uncertain," and have recommended contrast enhanced computed tomography (CECT) but not FDG PET/CT as a routine imaging test for CCA workup. We set out to compare the diagnostic performance of FDG PET/CT and CECT in patients with CCA. The retrospective study included patients with CCA who underwent FDG PET/CT and CECT within 2-month interval between 2011 and 2013 in our hospital. Lesion-based comparison was conducted. Final diagnoses were made based on the composite clinical and imaging data with minimal 6-month follow-up. A total of 18 patients with 28-paired tests were included. There is a total of 142 true malignant lesions as revealed by the 6-paired pre-treatment and 22-paired post-treatment tests. On a lesion-based analysis, the sensitivities, specificities, positive predictive values (PPVs), negative predictive values (NPVs), and accuracies of PET/CT and CECT for detection of CCA were 96.5%, 55.5%, 97.2%, 50.0%, 94.1% and 62.2%, 66.7%, 96.7%, 10.0%, 62.5%, respectively. FDG PET/CT detected more intrahepatic malignant and extrahepatic metastases; and had significant higher sensitivity, NPV, and accuracy than CECT, while similar in specificity and PPV. No true positive lesion detected on CECT that was missed on PET/CT, and none of the false negative lesions on PET/CT were detected on CECT. Six patients had paired pretreatment tests, and FDG PET/CT results changed planned management in three patients. Our data suggest that FDG PET/CT detect more primary and metastatic lesions and lead to considerable changes in treatment plan in comparison with CECT.